Pengaruh Model Pembelajaran Kooperatif Tipe Team Games Tournament terhadap Hasil Belajar Kognitif dan Psikomotorik Passing Bawah Bola Voli Siswa Sekolah Dasar - Muzaedi, Ahmad; Yusuf, Rusdiana; Aminullah, Aminullah (Sportify Journal, 2023)
Penelitian ini bertujuan mengetahui pengaruh model pembelajaran kooperatif tipe Team Games Tournament (TGT) terhadap hasil belajar kognitif dan psikomotorik passing bawah bola voli siswa kelas V SDN Peresak Bebuak. Penelitian menggunakan desain quasi experimental tipe nonequivalent control group design. Sampel berjumlah 51 siswa, terdiri atas 25 siswa kelas eksperimen dan 26 siswa kelas kontrol. Data dikumpulkan melalui tes tulis 12 butir dan tes unjuk kerja passing bawah. Hasil menunjukkan rata-rata kognitif kelas eksperimen meningkat dari 65,72 menjadi 78,64, sedangkan kontrol dari 65,32 menjadi 71,64. Rata-rata psikomotorik eksperimen meningkat dari 58,92 menjadi 73,60, sedangkan kontrol dari 61,96 menjadi 68,84. Uji Mann–Whitney menunjukkan perbedaan signifikan (p = 0,015). Model TGT direkomendasikan sebagai alternatif pembelajaran PJOK yang aktif, kolaboratif, dan kompetitif. The Effect of the Team Games Tournament Cooperative Learning Model on Elementary Students’ Cognitive and Psychomotor Learning Outcomes in Volleyball Underhand Passing Abstract This study aimed to examine the effect of the Team Games Tournament (TGT) cooperative learning model on Grade V students’ cognitive and psychomotor learning outcomes in volleyball underhand passing at SDN Peresak Bebuak. A quasi-experimental nonequivalent control group design was employed. The sample consisted of 51 students, including 25 students in the experimental class and 26 students in the control class. Data were collected using a 12-item written test and a performance-based underhand passing test. The results showed that the experimental class cognitive mean increased from 65.72 to 78.64, while the control class increased from 65.32 to 71.64. The experimental psychomotor mean increased from 58.92 to 73.60, while the control class increased from 61.96 to 68.84. The Mann–Whitney test indicated a significant difference (p = .015). TGT is recommended as an active, collaborative, and competitive alternative for physical education learning.